Development of chemical markers and chromatographic fingerprint of Clinachantus nutans for evaluation of therapeutic products - Hazrulrizawati, Abd Hamid; Mashitah, Mohd Yusoff (2016)
Clinacanthus nutans has attracted Malaysian public interest due to its high medicinal values in the prevention of cancer. The extraction was done by MeOH at room temperature while chromatography was done on a silica gel RP-18. Six fractions collected from column chromatography were evaluated by the MTT assay against two breast cancer cell lines: MDA-MB-231 and MCF-7. Amongst the fractions, A12 and A17 were shown to exhibit the most activity, and the compounds were mostly isolated from these fractions. Two sulphur-containing compounds, entadamide C and clinamide D were isolated. Molecular docking simulation studies revealed that entadamide C and clinamide D could bind favourably to the caspase-3 binding site with the binding energy of -4.28 kcal/mol and -4.84 kcal/mol, respectively.